Integral Research Framework for Sustainable Structures for Future - Kulasuriya, Chandana; Vimonsatit, Vanissorn (Engineers Australia, 2012)
This paper describes philosophical underpinnings of the discourse of sustainable structures through the passage from past to present to future. Research paradigms that have been influenced by the scientific revolution occurred in the modern era consider reality as a single external entity and hence sustainability is viewed from an objective angle. Accordingly such research studies mainly focus on physical entities such as resource efficiency and new technologies, but do not pay much attention towards other forms of realities, namely, subjective reality and inter-subjective reality such as aesthetic sustainability and cultural sustainability. Post-modernism that emerged as a reaction to modernism recognises other realities. Post-modern research paradigms tend to recognise many aspects related to sustainability but not in a total integrated way. In the dawn of the new millennium, we have entered the era of Post-post-modernism which integrates multiple realities. Within the Post-post-modern movement, American Philosopher Ken Wilber is a leading figure who introduced 'Integral Theory' and general 'All Quadrants All Levels Framework' (AQAL Framework). This paper explores the possibility of employing the general AQAL framework for research relating to sustainable structures. This paper presents how AQAL framework can be used to develop a research framework for achieving integral sustainability.